Bilateral transverse facial clefts (congenital macrostomia) - A case report - Okpokowuruk FS; Amanari OC (Ibom Medical Journal, 2013)
We describe a very rare case of bilateral congenital macrostomia in a three month old female infant with an unusual association of brachycephaly and other dysmorphic features as a result of ingestion of an alcohol based herbal preparation, Sulphadoxine-Pyrimethamine and probably supplemental doses of Vitamin E in the early first trimester of pregnancy. This case report emphasizes the need for maternal education and support of maternal health care.